2019
DOI: 10.3390/ma13010032
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature-Processed Amorphous Sn-In-O Electron Transport Layer for Perovskite Solar Cells

Abstract: We report amorphous tin-indium-oxide (TIO, Sn fraction: >50 atomic percentage (at%)) thin films as a new electron transport layer (ETL) of perovskite solar cells (PSCs). TIO thin films with Sn fraction of 52, 77, 83, 92, and 100 at% were grown on crystalline indium-tin-oxide (ITO, Sn fraction: ~10 at%) thin films, a common transparent conducting oxide, by co-sputtering In2O3 and SnO2 at room temperature. The energy band structures of the amorphous TIO thin films were determined from the optical absorbance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It is generally known that charge recombination is highly responsible for reducing the energy conversion efficiency of PSCs. Many researchers have focused on the ETL of PSCs [16,17,27]. Some investigators have tried to add a new layer into the ETL to form a bilayer, which has been demonstrated as an effective way to modify the interfacial behavior and photovoltaic performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that charge recombination is highly responsible for reducing the energy conversion efficiency of PSCs. Many researchers have focused on the ETL of PSCs [16,17,27]. Some investigators have tried to add a new layer into the ETL to form a bilayer, which has been demonstrated as an effective way to modify the interfacial behavior and photovoltaic performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The produced ZSO nanoparticle-based PSCs exhibited a PCE of 15.3%. 122 Subsequently, a solution-processed ZSO-lm was employed by Jung et al 123,124 as an ETL in a PSC, resulting in a record-breaking efficiency of 20.02%. Recently, Zheng et al 125 created a Zn 2 SnO 4 single crystal using a straightforward, affordable hydro-thermal synthesis process.…”
Section: Tin (Sn)-based Pscsmentioning
confidence: 99%